2017
DOI: 10.1038/ncomms15559
|View full text |Cite|
|
Sign up to set email alerts
|

Leukocyte integrin Mac-1 regulates thrombosis via interaction with platelet GPIbα

Abstract: Inflammation and thrombosis occur together in many diseases. The leukocyte integrin Mac-1 (also known as integrin αMβ2, or CD11b/CD18) is crucial for leukocyte recruitment to the endothelium, and Mac-1 engagement of platelet GPIbα is required for injury responses in diverse disease models. However, the role of Mac-1 in thrombosis is undefined. Here we report that mice with Mac-1 deficiency (Mac-1−/−) or mutation of the Mac-1-binding site for GPIbα have delayed thrombosis after carotid artery and cremaster micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
120
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(125 citation statements)
references
References 80 publications
4
120
0
1
Order By: Relevance
“…Leucocyte integrin CD11b is a marker of neutrophil activation and crucial for leucocyte recruitment to endothelium . Moreover, CD11b binding with GPIbα is indispensable in arterial thrombus formation .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Leucocyte integrin CD11b is a marker of neutrophil activation and crucial for leucocyte recruitment to endothelium . Moreover, CD11b binding with GPIbα is indispensable in arterial thrombus formation .…”
Section: Resultsmentioning
confidence: 99%
“…Leucocyte integrin CD11b is a marker of neutrophil activation and crucial for leucocyte recruitment to endothelium. 27 Moreover, CD11b binding with GPIbα is indispensable in arterial thrombus formation. 7 We found that HDC −/− platelets led to an increase in CD11b expression in WT neutrophils, while HDC −/− neutrophils exhibited high CD11b expression levels prior coincubation with platelets ( Figure 5C), suggesting an abnormal expression of integrin on HDC −/− neutrophils.…”
Section: Hdc −/− Platelets Increase Neutrophil-platelet Interactionsmentioning
confidence: 99%
“…Tissue NETs cause platelet activation and thrombosis, possibly from NET-associated histones that can induce platelet aggregation through toll-like receptors (TLRs) on platelets and other cells. Platelet signaling activates the major platelet adhesion receptor, integrin αIIbβ3, which mediates NETs are an ideal foundation or template for binding activated platelets, erythrocytes and leukocytes, activating factor XI and generating thrombin for fibrin production platelet aggregation, as well granule release, phosphatidylserine exposure, FV/Va expression and thrombin generation [43][44][45]. NETs are recognized as linking inflammation, coagulation and thrombosis both locally and systemically in multiple conditions [46].…”
Section: Nets As a Unifying Theme In Covid-19 Infection And Thrombosimentioning
confidence: 99%
“…Platelet‐neutrophil aggregation is mediated by interactions between neutrophil integrin CD11b/CD18 (Mac‐1) and platelet glycoprotein Ibα (GPIbα) (Simon et al , ; Ehlers et al , ). The importance of this interaction in the context of VTE is further emphasised by recent studies in which mice deficient in Mac‐1, or that only express mutant GPIbα that is defective for Mac‐1 binding, exhibit significantly smaller thrombi in murine thrombosis models (Wang et al , ). Pertinently, these mice exhibited no obvious haemostatic defects, indicating inhibition of the Mac‐1/GPIbα interaction represents an exciting antithrombotic target, that, if pharmacologically targeted, is predicted to cause minimal impact on normal haemostasis (Plow et al , ).…”
Section: How Do Circulating Blood Cells Contribute To Vte Development?mentioning
confidence: 99%
“…The increased understanding of the contribution of innate immune cells to VTE also offers new possibilities. In particular, efforts to inhibit platelet‐neutrophil interactions via key receptor blockade are likely to be of interest (Wang et al , ). Moreover, agents that pharmacologically regulate NET generation or facilitate their degradation within clots may also be of benefit (Lewis et al , ; Jiménez‐Alcázar et al , ).…”
Section: Potential Antithrombotic Drugs Of the Future?mentioning
confidence: 99%